Pharmacogenomics guidelines: Current status and future development. (16th May 2019) - Guo, Chengxian; Xie, Xiaoxue; Li, Jingao; Huang, Lihua; Chen, Shaojun; Li, Xi; Yi, Xin; Wu, Qin; Yang, Guoping; Zhou, Honghao; Liu, Jun‐Ping; Chen, Xiang
Abstract: Genetic polymorphisms impact biological responses to drugs. Current pharmacogenomics guidelines formulated by different countries, such as the Clinical Pharmacogenetics Implementation Consortium, the Dutch Pharmacogenetics Working Group, the Canadian Pharmacogenomics Network for Drug Safety, and the French National Network (Réseau) of Pharmacogenetics, play important roles in clinical practices. However, the standards for these guidelines vary significantly, resulting in differences in recommendations. The present article discusses these differences by head‐to‐head comparison of the existing pharmacogenomics guidelines and proposes new strategies for their future development.